Juridical Analysis of Legal Protection Against Disadvantaged Sellers in E-Commerce Transactions on the Tokopedia Online Shopping Site - Septian Dwi Andini; Retno Nilasari (UM Purwokerto Press, 2023)
This study aims to analyze the legal protection of sellers who suffer losses due to consumer actions and legal actions that can be taken by sellers on the Tokopedia e-commerce platform regarding the return of goods that are not carried out by buyers after the refund is returned, which has an impact on seller losses. The research method used in this research is the normative juridical method, by collecting data from literature studies, including laws, regulations, and related court decisions. The results show that legal protection for sellers is contained in Law Number 8 of 1999 concerning Consumer Protection, which protects the rights of sellers and emphasizes the importance of consumer good faith in transactions. In addition, buyer fraud is also protected by Article 378 of the Criminal Code. In resolving disputes, sellers can choose out-of-court settlement and report disputes to Tokopedia through the